Caffeine's complex influence on the attraction effect: a mixed bag of outcomes - Michael Canty; Felix Josua Lang; Susanne Jana Adler; Marcel Lichters; Marko Sarstedt (Marketing Letters, 2023)
Psychological state alterations induced by substance-related physiological mechanisms affect consumer decision-making. We examine the influence of caffeine—the world's most popular psychostimulant—on the attraction effect. In three double-blinded experiments, we show that caffeine intake via coffee influences consumers' preference for product options that asymmetrically dominate a decoy option in choice sets (i.e., the attraction effect). Using real products in consequential choice tasks, we show that high caffeine intake (200~mg) is associated with a larger attraction effect both on between-subjects and within-subjects levels and in free-choice as well as forced-choice decision tasks. On the contrary, we do not find support for caffeine's influence on the attraction effect when considering intermediate levels of caffeine intake (125~mg) and hypothetical decisions. We discuss theoretical implications for context effect research and practical implications for marketers.
Keywords: 380; Asymmetric dominance; Attraction effect; Caffeine; Context effects; Preference reversal; Repulsion effect